Graphene-based composites for biomedical applications - Selsabil Rokia Laraba; Wei Luo; Amine Rezzoug; Qurat ul ain Zahra; Shihao Zhang; Bozhen Wu; Wen Chen; Lan Xiao; Yuhao Yang; Jie Wei; Yulin Li (Green Chemistry Letters and Reviews, 2022)
Over the last decade, the superior properties of graphene have contributed to intensive studies on the fabrication and applications of graphene nanocomposites. Ex-situ homologous recombination and recombination techniques were listed. Because of their remarkable features, including thermal conductivity and high-specific area, graphene and its derivatives have a significant prospective for medical and biological applications, including drug delivery and bio-imaging. The usage of graphene-based nanomaterials is a hot topic in medicinal research. Many research studies have been performed on graphene-based composites, but only a few reviews have been published regarding their applications in the biomedical field and potential risk factors associated with human well-being and the environment. Hence, this review paper aims to provide in-depth information on ongoing knowledge and results about the properties of graphene-based composites. The discovery, developmental methods, structural properties, and synthesis of graphene nanomaterials have been discussed. After a brief description of the most common methods used for fabricating or extracting graphene derivatives, the main steps of graphene-based composite preparation are introduced. Applications of graphene-based composites in drug delivery, medical, and biomedical fields have been addressed. Finally, the future perspectives and challenges associated with the applications of graphene-based composites have been summarized.Highlights Compositions and characteristics of nanocomposite materials reinforced with graphene, graphene oxide, reduced graphene oxide, and modified graphene.The synthesis method of graphene and the manufacturing of graphene-based composites.Latest developments in graphene-based composites for biomedical applications.Consequences of the large-scale production of graphene-based composites.